Penerapan Model Pembelajaran Role Playing Dalam Mata Pelajaran PKn Untuk Meningkatkan Hasil Belajar Murid Kelas V SD Inpres Jatia Kecamatan Bajeng Kabupaten Gowa - Nasrun Hasan; Nursalam Nursalam (Universitas of Muhammadiyah Makassar, 2017)
The problem in this research is how to use Role Playing Learning model in improving Student's learning outcomes of V class V SD Inpres Jatia Kel. Mataallo Kec. Bajeng Kab. Gowa.Tujuan to be achieved in this research is to know the model of learning Role Playing in improving the results of learning PKN class V elementary school Inpres Jatia Kel. Mataallo Kec. Bajeng Kab. Gowa. This research includes qualitative descriptive research designed through classroom action research. This classroom action research is conducted in two cycles, each cycle is held 4 times. This research was conducted in class V Primary element of Inpres Jatar Kel. Mataallo Kec. Bajeng Kab. Gowa. Subjects of this study amounted to 31 people. The instrument of this research is test and observation sheet. Data were analyzed quantitatively and qualitatively. The results showed that the use of Model Role Playing can improve the learning outcomes of Civics on the subject Keeping the Unity of the Republic of Indonesia. In cycle I, the average student activity is categorized less and increased in cycle II with high category. The results of the first cycle test average of 61.09 and increased in cycle II to 77.25. The completeness of learning cycle I as much as 32.25% and increased in cycle II to 77.45%.Keywords: Model Role Playing and Learning Outcomes Civics